LIVING QUR’AN IN ANNYORONG LOPI PINISI TRADITION: AN ANTHROPOLOGICAL STUDY OF THE QUR’AN - Asfar, Khaerul; Abubakar, Achmad; Pababbari, Musafir; Sabry, Muhammad Sadiq (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
The purpose of this research is to find the implementation of living Qur’an in Annyorong Lopi (boat launch) Pinisi tradition in Bulukumba. This research is a qualitative descriptive study with an anthropological approach to the Qur’an. Primary data sources were obtained from Panrita Lopi (boat maker), boat entrepreneur, religious figure, cultural figure, and local government. Data was collected through a series of observation methods, interviews, documentation, secondary data from literature books, journals, the internet, and other complementary data. The research results found the implementation of living Qur’an in Annyorong Lopi (boat launch) Pinisi tradition, which are the values of the Qur’an that live amid Panrita Lopi (boat marker) society by analyzing the recitation of dialect Konjo language prayers derived from the Qur’an. It also found the implementation of anthropology of the Qur’an reviewed from the sociological aspect and the phenomenological aspect in the process of making Pinisi boats to the Annyorong Lopi (boat launch) tradition. The tradition of Annyorong Lopi (boat launch) Pinisi is done as a proof of gratitude and prayer of salvation for the completion of the Pinisi boat.الملخصيهدف هذا البحث إلى إيجاد تنفيذ القرآن الحي في تقليد Annyorong Lopi Pinisi (إطلاق السفينة) في بولوكومبا. يستخدم هذا البحث بالنهج الأنثروبولوجي القرآن. مصادر البيانات الأساسي التي تم الحصول عليها من Panrita Lopi (صانع السفينة) ورائد الأعمال في السفينة والشخصية الدينية و الثقافي والحكومة المحلية. البيانات التي تم جمعها من خلال سلسلة من أساليب المراقبة والمقابلات والوثائق والبيانات الثانية من الكتب والمجلات والإنترنت وغيرها من البيانات التكميلية. وجدت نتائج هذا البحث إلى إيجاد تنفيذ القرآن الحي في تقليد Annyorong Lopi Pinisi أن هناك قيم القرآن الكريم التي تعيش في وسط Panrita Lopi (صانع السفينة) المجتمع من خلال تحليل تلاوة الدعاء بالهجة اللغة Konjo وهي المستمدة من القرآن. وجدت أن تنفيذ الأنثروبولوجيا من القرآن استعرض من الجانب الاجتماعي و الجانب الظاهري في عملية صنع السفينةPinisi حتى تقليدAnnyorong Lopi . تقليدAnnyorong Lopi Pinisi يتم كدليل على الامتنان والدعاء السلامة من البلاء من أجل الخلاص لاستكمال السفينة Pinisi.